Métodos y estrategias docentes en el proceso de enseñanza de la lectura y escritura de estudiantes de primer grado en una escuela pública - Rodriguez Reyes, Trilce Junnet (2023)
Reading and writing is defined as the ability to read and write, whose objective is the interpretation of various textual materials using the written code, to finally reflect the language. These skills are complex to consolidate and are integrated into student learning from their first years of preparation, which will accompany them throughout their lives. In this sense, the selection of different methods and strategies for the consolidation of these skills is crucial. Mastery of reading and writing will provide students with new ways of communicating and the development of various skills such as fine motor skills, hand-eye coordination, and creativity. In this way, reading and writing become one of the vital processes in the school stage and is consolidated as the basis of consequent learning, in addition to developing language and intelligence, it enhances skills related to oral and written expression. In view of the health emergency generated by COVID-19, the educational system proposed different didactic adaptations for these aspects from the remote modality and thus, generate new educational resources for learning reading and writing under a new presence. This research concludes that the informants recognize the importance of using different methods and strategies for teaching reading and writing, as well as the resources and the educational context in which this learning takes place.